2021
DOI: 10.1097/aln.0000000000004092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in the Dorsal Root Ganglion during the Late Phase of Peripheral Nerve Injury–induced Pain in Rodents: A Systematic Review

Abstract: The dorsal root ganglion is widely recognized as a potential target to treat chronic pain. A fundamental understanding of quantitative molecular and genomic changes during the late phase of pain is therefore indispensable. The authors performed a systematic literature review on injury-induced pain in rodent dorsal root ganglions at minimally 3 weeks after injury. So far, slightly more than 300 molecules were quantified on the protein or messenger RNA level, of which about 60 were in more than one study. Only n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Stephens et al use naïve rats as the control group, and thus may presumedly capture gene expression changes not only associated with nerve constriction injury but also with skin incision, nerve terminal damage, and inflammatory response of deep muscle tissue. Besides, the two studies took 11 days and 14 days post-CCI as endpoints respectively, both of which were considered to be in the maintenance phase of NP [ 14 ]; however, the fact that transcriptional changes are dynamic in nature might also help to explain the distinction. Furthermore, a different number of biological replicates, heterogeneity between studies with respect to high-throughput platform, ligature, and tightness of ligation, etc., might also contribute to the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephens et al use naïve rats as the control group, and thus may presumedly capture gene expression changes not only associated with nerve constriction injury but also with skin incision, nerve terminal damage, and inflammatory response of deep muscle tissue. Besides, the two studies took 11 days and 14 days post-CCI as endpoints respectively, both of which were considered to be in the maintenance phase of NP [ 14 ]; however, the fact that transcriptional changes are dynamic in nature might also help to explain the distinction. Furthermore, a different number of biological replicates, heterogeneity between studies with respect to high-throughput platform, ligature, and tightness of ligation, etc., might also contribute to the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray or RNA sequencing (RNA-seq), preclinical studies have investigated transcriptome profiles of mRNA and non-coding RNA in the DRG of different peripheral nerve injury (PNI) induced-NP models, including widely used sciatic nerve chronic constriction injury (CCI), spared nerve injury, spinal nerve ligation, partial sciatic nerve ligation, etc. [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Studies focusing on DRG transcriptome in the context of CCI-induced NP were scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed several DEGs associated with pain or emotional dysfunction, including GPCRs and ion channels. Npy, one of the upregulated GPCRs in the DEGs, was found to be elevated in the dorsal root ganglia and spinal cord, indicating a compensatory response to nerve damage ( Basu et al, 2022 ; Chalaki et al, 2022 ). Additionally, the GPR151 receptor in nociceptors was identified to regulate P2X3 function and microglial activation, thereby modulating NP ( Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Galanin is involved in several biological processes,16 20 including nociceptive sensory processing in the spinal cord. Galanin and neuropeptide Y are consistently upregulated on both gene and protein levels in dorsal root ganglia (DRG) in rodents with a potential relation to pain after a severe nerve injury,21–23 a symptom which may also be present among individuals with HAVS 24 25. Experimental studies in rats also indicate that a sciatic nerve compression, which is a less pronounced injury, increases the number of galanin-stained sensory neurons in DRG compared with uninjured and contralateral sensory neurons 26.…”
Section: Discussionmentioning
confidence: 99%